Standing Still at Full Speed: Sports in an Overheated World - Eriksen, Thomas Hylland (Frontiers in Sports and Active Living, 2021)
In evolutionary biology, the Red Queen Effect refers to a particular aspect of competition (van Valen, 1973) or a long-term result of sexual selection. As in the situation involving Alice and the Red Queen, an organism, or species, is forced to evolve continuously merely to survive, since its competitors, prey or predators evolve. As rabbits become faster, foxes have to follow suit in the longue durée of evolution. An organism has to evolve merely to retain its niche, simply because its prey, predators or competitors evolve. The decision-makers in the world of competitive sport have no choice but to play according to the rules, trying to gain those extra inches enabling them to catch more sunlight, as it were, than their close neighbours. While this form of competition is integral to capitalist growth and what is known as progress, it is also, as a guiding principle for life and economic activity, a recipe for ecological disaster. It encapsulates, in a nutshell, the double bind of contemporary industrial capitalism, suspended in mid-air between growth imperatives and a desire for sustainability. The world of competitive sports is not just an integral part of global capitalism, but it also mirrors and mimes its internal logic. The kinship between sport and war is obvious, and many sports grew out of military training. But since much of the world has been spared the horrors of war for generations, in the very same period that capitalism has become ever more hegemonic and globalised, sports in the 21st century have come to resemble market competition more than bloody events on the battlefield. Not least for this reason, the treadmill paradox, or Red Queen phenomenon, easily discernable in market economies as a driver for change, whether progressive or destructive, can fruitfully be applied as an analytical lens through which to view sport.